2017
DOI: 10.1007/s12665-017-6560-6
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical approach to hydrological model calibration

Abstract: Hydrological models have been widely used for water resources management. Successful application of hydrological models depends on careful calibration and uncertainty analysis. Spatial unit of water balance calculations may differ widely in different models from grids to hydrological response units (HRU). The Soil and Water Assessment Tool (SWAT) software uses HRU as the spatial unit. SWAT simulates hydrological processes at sub-basin level by deriving HRUs by thresholding areas of soil type, land use, and slo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The majority of studies reported that the delineation scenarios resulted in only minor or negligible effects on SWAT-predicted streamflow (Table 1). However, some studies described streamflow effects estimated with SWAT that were influenced by the various simulated delineation scenarios [11,15,20,22,[30][31][32]. Several of these studies noted that the effects on streamflow were relatively stable for more refined delineation schemes, but that the accuracy of the streamflow estimates declined for coarser HRU and/or subbasin subdivisions (e.g., [11,15,20]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of studies reported that the delineation scenarios resulted in only minor or negligible effects on SWAT-predicted streamflow (Table 1). However, some studies described streamflow effects estimated with SWAT that were influenced by the various simulated delineation scenarios [11,15,20,22,[30][31][32]. Several of these studies noted that the effects on streamflow were relatively stable for more refined delineation schemes, but that the accuracy of the streamflow estimates declined for coarser HRU and/or subbasin subdivisions (e.g., [11,15,20]).…”
Section: Introductionmentioning
confidence: 99%
“…The size of systems analyzed in these studies ranged from 6.2 km 2 /6.3 km 2 to in Indiana/Germany to 17,941 km 2 in Iowa ( Table 1). The level of detail incorporated in these different assessments also varied considerably, with large ranges of HRUs and/or subbasins used in some studies (e.g., [13,14,16,27]) versus limited detail in other studies [12,31]. For small watersheds, the landscapes may not be complex enough to detect the runoff variation caused by different delineation schemes.…”
Section: Introductionmentioning
confidence: 99%
“…It also provides a platform to implement other algorithms. For example, a hierarchical approach to calibration was implemented on this software (Ozdemir et al, ). For future research, choosing the most sensitive parameters will be performed by automated analysis of flow patterns.…”
Section: Discussionmentioning
confidence: 97%
“…MATLAB is chosen for developing the tool since it allows to implement, test and debug algorithms easily, and to perform extensive data analysis and visualization. FACT was also used for implementing a hierarchical approach for calibration (Ozdemir et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Manuscript 6 entire catchment (lumped or distributed) parameters according to model predictive performance at the basin outlet assessed via single or multiple objectives. Some authors have proposed advancing the single site calibration with a sequential/hierarchical approach (Hay et al, 2006;Ozdemir et al, 2017;Singh & Bárdossy, 2015). While the first authors sequentially calibrate a model"s performance of potential evapotranspiration, water balance, and daily runoff , the second authors divided sub-basins into two hydrologic response units (HRU) and two further child HRUs based on influential parameters such as curve number and hydraulic conductivity.…”
Section: Accepted Manuscriptmentioning
confidence: 99%